Make your own disinfectant - Goh, Choon Fu; Long, Chiau Ming * (Star Media Group Berhad, 2020)
Using disinfectant to keep our surroundings virus-free and hygienic during this Covid-19 pandemic has become standard practice at home and the workplace. While commercial disinfectants are available, you can actually make your own from household liquid bleach.